The Effects of Corruptionon Growth, Investment, and Government Expenditure - Mauro, Paolo (International Monetary Fund, 1996)
This paper discusses the possible causes and consequences of corruption. It provides a synthetic review of recent studies that analyze this phenomenon empirically. In addition, it presents further results on the effects of corruption on growth and investment, and new cross-country evidence on the link between corruption and the composition of government expenditure